Alternative Design to Prevent Disharmony Between Regional Heads and Regional House of Representatives - Ahmad Siboy; Al-Fatih, Sholahuddin; Tinuk Dwi Cahyani (Universitas Ahmad Dahlan, 2024)
Regional heads and Regional House of Representatives (DPRD) are local government. Both institutions were formed in order to support the running of local government within the framework of checks and balances. However, in practice, the relationship between the two institutions tends to be destructive and intrigue each other and result in a convergence of the priorities of the interests of the people. This research departs from questions about what are the factors that cause the fracture of relations between regional heads and DPRD, what are the implications of disharmony between regional heads and DPRD and how to design to prevent disharmony between regional heads and DPRD in the future. This research is qualified into the type of normative juridical research with a statutory approach, a case approach, and a conceptual approach. The results showed that the disharmony between the regional head and the DPRD was caused by the process of directly electing the regional head so that the regional head felt that they did not have a debt of gratitude to the DPRD. At the same time, at the time of nomination, the elected regional heads sometimes come from independent candidates and/or do not come from the majority party in the DPRD. In the future, the disharmony between regional heads and DPRD cannot be allowed to continue considering that the disharmony in relations has caused obstacles to the government. The design that can be taken to prevent disharmony in relations can be pursued by applying sanctions to regional heads and/or taking over temporary authority by superior organizations.